Social Support To Women With Breast Cancer Undergoing Treatment - Luthfiyyah Khanuun; Sri Nabawiyati Nurul Makiyah (Universitas Muhammadiyah Semarang, 2021)
Breast cancer treatment will have an impact on quality of life and social support that leads to interpersonal women with breast cancer. This study aims to explore and synthesize the scientific literature on the social support provided to women with breast cancer who underwent treatment in the hospital. The studies use 4 databases are PubMed, EBSCO, Science Direct, and Google Scholar. The main keywords are "Breast cancer", "Social support", "Oncological treatment", "Qualitative Research". The search article was carried out in accordance with the guideline of PRISMA. The findings in this study contained 4 main themes from 6 articles. Research findings include family support, emotional response support, support for finding and accessing information, communicating with health care professionals, and support for meeting unmet needs. This support began to be felt since the patient was first diagnosed with breast cancer. This is very real and accepted support that has a positive impact on the lives of women with breast cancer.